Effect of hygrothermal ageing on the compressive behavior of glass fiber reinforced IPN composite pipes. (2021) - Srinivasan, T.; Suresh, G.; Ramu, P.; Vignesh, R.; Vijay Harshan, A.; Vignesh, K.P.
Abstract: The influences of hygrothermal ageing on the compressive behavior of the glass fiber reinforced interpenetrating polymer network (IPN) composites were discussed. Specimens with different proportions of polyurethane (PU) prepolymer with Vinylester (VER) were fabricated by hand – layup technique then the tubes were hygrothermally aged in water at different temperatures of 55 °C, 65 °C, 75 °C for periods of 500, 1000, 1500, 2000 h. Uniaxial compressive tests were performed on the dry and aged sample by using a universal testing machine as per the ASTM D695-10 standard in room temperature to absorb the response of the tubes at standard temperatures. The relationships between the dry specimens with the aged specimens were determined. The absorbed results shown that the strength of the GFRP tubes slightly decreases with increase of the temperature and with respect to corresponding ageing period. Further the geometric structure of the specimen retains, as much as % of PU prepolymer increases into the IPN system.